2009
DOI: 10.1039/b908241g
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-activated C-peptide resistance to the type 2 diabetic erythrocyte is associated with hyperglycemia-induced phosphatidylserine externalization and reversed by metformin

Abstract: Insulin resistance can broadly be defined as the diminished ability of cells to respond to the action of insulin in transporting glucose from the bloodstream into cells and tissues. Here, we report that erythrocytes (ERYs) obtained from type 2 diabetic rats display an apparent resistance to Zn(2+)-activated C-peptide. Thus, the aims of this study were to demonstrate that Zn(2+)-activated C-peptide exerts potentially beneficial effects on healthy ERYs and that these same effects on type 2 diabetic ERYs are enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 49 publications
(70 reference statements)
2
45
0
Order By: Relevance
“…Figure 3 presents the effect of the different Cpeptide fragments on erythrocyte deformability, and the inhibition with oubain or EDTA at a shear stress rate of 1.2 Pa. In a type 2 diabetes rat model, Zn 2+ -activated C-peptide was shown to exert less ATP release from erythrocytes, as compared with controls [46]. Pretreatment of the type 2 diabetic erythrocytes with metformin restored the C-peptide-stimulated release of ATP from the erythrocyte.…”
Section: Effect Of C-peptide On Red Blood Cell Elasticitymentioning
confidence: 99%
“…Figure 3 presents the effect of the different Cpeptide fragments on erythrocyte deformability, and the inhibition with oubain or EDTA at a shear stress rate of 1.2 Pa. In a type 2 diabetes rat model, Zn 2+ -activated C-peptide was shown to exert less ATP release from erythrocytes, as compared with controls [46]. Pretreatment of the type 2 diabetic erythrocytes with metformin restored the C-peptide-stimulated release of ATP from the erythrocyte.…”
Section: Effect Of C-peptide On Red Blood Cell Elasticitymentioning
confidence: 99%
“…Previous studies involving C-peptide interactions with RBCs clearly demonstrate that Cpeptide is able to stimulate glucose uptake into the RBC, resulting in the release of ATP into the extracellular matrix [18,52]. This glucose uptake results in an increase of ATP production by the RBC.…”
Section: C-peptide: a Multi-tasking Molecule Or Stimulus Of Such?mentioning
confidence: 99%
“…A small scale study involving RBCs obtained from a rat model of type 1 diabetes revealed that the overall percentage increase in ATP release was not statistically different to the release measured from RBCs obtained from control rats [18]. In contrast, in a rat model of type 2 diabetes, ATP release from these cells were significantly less (approximately 50%) than that obtained from control RBCs [18]. Subsequent studies suggested that exogenously added C-peptide was interacting with the RBCs obtained from the type 2 rat models to a much lesser extent than the control RBCs (again, approximately a 50% reduction).…”
Section: Effects Of C-peptide On Cells In the Bloodstreammentioning
confidence: 99%
See 2 more Smart Citations